Evaluasi Kebijakan Badan Usaha Milik Desa (BUMDES) Makmur Sejahtera di Desa Salatiga Kecamatan Salatiga Kabupaten Sambas - Wulandari Wulandari; Zulkarnain Zulkarnain; Arifin Arifin (Public Inspiration : Jurnal Administrasi Publik, 2026)
This study aims to evaluate the implementation of the Makmur Sejahtera Village-Owned Enterprise (BUMDes) policy in Salatiga Village, Salatiga Subdistrict, Sambas Regency, during the 2017–2022 period. As an instrument for strengthening the village economy, BUMDes is expected to improve community welfare and Village Owned Revenue (PADes); however, its performance has not yet yielded optimal results. This study employs a descriptive qualitative approach using the evaluation model proposed by Rossi, Lipsey, and Freeman (2004), which encompasses needs assessment, program design, implementation process, impact, and efficiency. The research results indicate that the management policies of BUMDes Makmur Sejahtera have not been optimally implemented across all evaluation dimensions. The establishment of BUMDes was not based on systematic mapping of community needs, business planning lacked support from measurable business plans, and program implementation continues to face limitations in management capacity, high turnover in leadership, and insufficient guidance. The resulting economic impact remains limited and has not been felt evenly by the community. Of the total capital contribution of Rp585,000,000, the contribution to the Village Revenue (PADes) reached only Rp32,995,900 with an effectiveness ratio of 5.64 percent, indicating low efficiency in the utilization of village resources. This study recommends participatory mapping of community needs, the development of measurable business plans, capacity building for management, and improved guidance.